MOSCOW CONTEMPORARY - Bayer, Waltraud (2016)
The monograph is the first international study to analyze and describe the process of the post-Soviet contemporary art museums from 1992 to 2015. Based on exemplary case studies, it covers the heterogeneous museum-political development, both on the state as well as on the local Moscow level. In addition, it offers a comprehensive documentation of analogous and digital sources. Die Monografie ist international die erste Studie, die den Entstehungsprozess der postsowjetischen zeitgenössischen Kunstmuseen von 1992 bis 2015 analysiert und beschreibt. Anhand von konkreten Fallstudien zeigt sie exemplarisch die oft nicht synchron verlaufende museumspolitische Entwicklung auf staatlicher wie auf lokaler Moskauer Ebene. Sie enthält eine umfassende Quellendokumentation.